The role of Kyrgyzstan’s political elite in shaping socio-political cycles - Nurgul Kazak kyzy; Saikal Zhunushova; Kulnara Abdymomunova; Kunduz Niiazalieva; Gulzana Asanbaeva (Clío)
The purpose of the study is to analyse the factors driving the evolution of Kyrgyzstan’s political elite, particularly through the lens of its cyclical involvement in revolutionary events. The methodology involves a comprehensive examination of the political elite’s structure, legislative framework, historical events, and a comparative analysis with other Central Asian countries. The findings reveal that Kyrgyzstan’s political elite remains entrenched in a clan-based, elite-patronage system, characterized by elements of corruption, which perpetuate ineffective governance and cyclical political instability. The study highlights the paradox of frequent revolutions, which reflect both a desire for democratic development and the difficulties of establishing a new political elite. Although Kyrgyzstan exhibits higher levels of female political participation than other Central Asian countries, significant gender gaps remain, emphasizing the need for stronger measures to ensure gender equality. Furthermore, the study observes a decline in press freedom, signalling a retreat from democratic principles and free speech.